SYNERGISTIC EFFECT OF MACUNA PRURIENS AND CURCUMA LONGA IN ROTENONE INDUCED PARKINSON DISEASED ANIMAL MODEL - ANIRUDDHA KULKARNI; MANOJ TARE; MEERA SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Parkinson’s disease (PD) is a brain disorder that causes unintended or uncontrollable movements, such as shaking, stiffness, and difficulty with balance and coordination. Symptoms usually begin gradually and worsen over time. As the disease progresses, people may have difficulty walking and talking. Recently, several herbal medicines have been tried for the treatment of such neurogenerative disorders. Studies on the extract of Macuna pruriens (MP) seeds and Curcuma longa (CL) rhizome have been done for better management of Parkinson’s disease. Methods: The combine effect of extracts of these herbs is studied on rotenone-induced PD on animal model. Both the plants were authenticated. Extracts of MP seeds and CL rhizome were prepared. These extracts were administered into rats to evaluate anti Parkinson’s activity. It was included with the catalepsy test, rota rod test, open field test, and estimation of dopamine in the brain. Results: The number of crossings was increased to 91.43±8.3 after the 28th of administration of both the extracts together. It is much higher than disease control and individual administration of extracts. After 28 days of animal study, attenuation of catalepsy behavior to 6.67±0.7 s was found with co-administration of both the extracts. The degree of prevention of fall-off time was much higher and significant on the 28th day of treatment, with 185.3±12.9 s in the groups treated with intranasal administration of the combination of both the extracts. The intranasal treatment with both the extracts elicited significantly higher elevation of brain dopamine content compared to the disease control group. Conclusion: This result showed that the Mp and Cl combination may be useful for better management of PD.